2011
DOI: 10.1088/0004-637x/744/2/81
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray Observations of the Young Pulsar J1357—6429 and Its Pulsar Wind Nebula

Abstract: We observed the young pulsar J1357-6429 with the Chandra and XMM-Newton observatories. The pulsar spectrum fits well a combination of an absorbed power-law model (Γ = 1.7 ± 0.6) and a blackbody model (kT = 140 +60 −40 eV, R ∼ 2 km at the distance of 2.5 kpc). Strong pulsations with pulsed fraction of 42% ± 5%, apparently associated with the thermal component, were detected in 0.3-1.1 keV. Surprisingly, the pulsed fraction at higher energies, 1.1-10 keV, appears to be smaller, 23% ± 4%. The small emitting area … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 49 publications
1
34
0
Order By: Relevance
“…In addition to those obtained from our observations, we collected γ-and X-ray best-fit spectra from the 2PC and papers published afterwards (PSR J1357−6429, Chang et al (2012); J1741−2054, Marelli et al (2014a); J1813−1246, Marelli et al (2014b); J0357+3205, Marelli et al (2013); J2055+2539, Marelli et al (in preparation)). Figure 2 reports the histogram of the Log(F γ /F X ) values for all pulsars, both RL and RQ, detected in the X-rays and with a nonthermal X-ray spectrum.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to those obtained from our observations, we collected γ-and X-ray best-fit spectra from the 2PC and papers published afterwards (PSR J1357−6429, Chang et al (2012); J1741−2054, Marelli et al (2014a); J1813−1246, Marelli et al (2014b); J0357+3205, Marelli et al (2013); J2055+2539, Marelli et al (in preparation)). Figure 2 reports the histogram of the Log(F γ /F X ) values for all pulsars, both RL and RQ, detected in the X-rays and with a nonthermal X-ray spectrum.…”
Section: Discussionmentioning
confidence: 99%
“…Deeper X-ray observations (Chang et al 2012;Lemoine-Goumard et al 2011) have firmly established X-ray pulsations with the pulsar period and found the tail-like structure to be extended out to several tens arcseconds from the pulsar. In addition, a fainter extended X-ray emission was detected on a few tens of arcminutes scale (Chang et al 2012;Abramowski et al 2011), showing a plerion-like structure, which is typical of many young pulsars. Finally, periodic pulsations of PSR J1357−6429 were discovered in the GeV range with Fermi (Lemoine-Goumard et al 2011), and an extended source, HESS J1356−645, associated with the pulsar has been found in the TeV range with H.E.S.S.…”
Section: Introductionmentioning
confidence: 97%
“…XMM-Newton and Chandra X-ray observations have revealed the pulsar X-ray counterpart and the pulsar wind nebula (PWN) containing a tail-like structure extended to several tens of arcseconds from the pulsar and a fainter plerion extended up to a few tens of arcminutes (Esposito et al 2007;Zavlin 2007;Chang et al 2012;Lemoine-Goumard et al 2011). The plerion was detected in the TeV range with the High Energy Stereoscopic System (H.E.S.S.)…”
Section: Introductionmentioning
confidence: 99%
“…Pulsations of J1357 with the pulsar period were discovered in X-rays with XMM-Newton and in the GeV range with Fermi ( Lemoine-Goumard et al 2011;Chang et al 2012). The pulsar X-ray spectrum shows a thermal component originating from the surface of the neutron star (NS) and a non-thermal power-law component describing the pulsar magnetosphere emission (Lemoine-Goumard et al 2011;Chang et al 2012;Danilenko et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation